PHYSICAL EDUCATION: THE POWER SIMBÓLICO IN SCHOOL (Fiep Bulletin - online, 2014)
This text covers Physical Education at the school, whose history is based on the history of capitalist society Brazil. All in the name of health and quality of life ... Do capitalism. We use a methodology to stamp covering qualitative observations, records, photographs, open interviews with parents, mothers, teachers, children and reflections on the daily life of classes in Physical Education with the object of the search seen as symbolic power invades the body of the child in a school of primary education of a periphery. We would have found another school: that of laughter, adventure, diversity, and plurality of ideas, constructive debate, and the collective complicity in a society that crushes the daily determines. We and the Singular But we found the opposite result. Bodies incarcerated, locked movements, minds silenced. Finally, we found the bodies of Death.
Keywords: Symbolic Power; body; physical education